Biocompatibility and Bioactivity of Four Different Root Canal Sealers in Osteoblastic Cell Line MC3T3-El - Nu-Ri Jun; Sun-Kyung Lee; Sang-Im Lee (The Korean Society of Dental Hygiene Science, 2021)
Background: Endodontic sealers or their toxic components may become inflamed and lead to delayed wound healing when in direct contact with periapical tissues over an extended period. Moreover, an overfilled sealer can directly interact with adjacent tissues and may cause immediate necrosis or further resorption. Therefore, the treatment outcome conceivably depends on the endodontic sealer's biocompatibility and osteogenic potential. This study aimed to evaluate the cell viability and osteogenic effects of four different sealers in osteoblastic cells.Methods: AH Plus (resin-based sealer), Pulp Canal Sealer EWT (zinc oxide-eugenol sealer), BioRoot RCS (calcium silicate-based sealer), and Well-Root ST (MTA-based calcium silicate sealer) were mixed strictly according to the manufacturer's instructions, and dilutions of sealer extracts (1/2, 1/5 and 1/10) were determined. Cell viability was measured using the water-soluble tetrazolium-8 (WST-8) assay. Differentiation was assessed by alkaline phosphatase (ALP) activity and mineralized nodule formation by Alizarin Red S staining.Results: The cell viability of the extracts derived from the sealers excluding Well-Root ST was concentration dependent, with sealer extracts having the least viability at a 1/2 dilution. At sealer extract dilution of 1/10, the test groups showed the same survival rate as that control group, with the exception of BioRoot RCS. Among all experimental groups, BioRoot RCS showed the highest cell viability after 48 hours. The ALP activity was significantly higher in a concentration-dependent manner. Furthemore, all four materials promoted ALP activity and mineralized nodule formation compared to the control at 1/10 dilutions.Conclusion: This is the first study to highlight the differences in biological activity of these four materials. These results suggest that the composition of root canal sealers appears to alter the form of biocompatibility and osteoblastic differentiation.